2007
DOI: 10.3201/eid1307.070063
|View full text |Cite
|
Sign up to set email alerts
|

Possible Zoonotic Transmission of Hepatitis E from Pet Pig to Its Owner

Abstract: Hepatitis E is transmitted mainly by water or food, but in industrialized countries, all routes of transmission have not been identified. We describe possible zoonotic transmission of hepatitis E virus that involved direct contact between a pet pig and its owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 14 publications
4
48
0
6
Order By: Relevance
“…Contact with feces from wild animals (wild boar and deer) could constitute a risk factor for HEV infection. In France, the risk factors identified as being associated with acute HEV infection include consumption of water from a private well or a nearby river (34), direct contact with pigs (33,47), and also hunting and residing in a rural area (22). Furthermore, the consumption of undercooked wild boar meat and liver, as observed with figatelli, a traditional pig liver sausage commonly consumed raw or undercooked in the south of France (5), and undercooked liver-based preparations, such as fressure from pigs, wild boar, and deer, could represent additional sources of infection for humans (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…Contact with feces from wild animals (wild boar and deer) could constitute a risk factor for HEV infection. In France, the risk factors identified as being associated with acute HEV infection include consumption of water from a private well or a nearby river (34), direct contact with pigs (33,47), and also hunting and residing in a rural area (22). Furthermore, the consumption of undercooked wild boar meat and liver, as observed with figatelli, a traditional pig liver sausage commonly consumed raw or undercooked in the south of France (5), and undercooked liver-based preparations, such as fressure from pigs, wild boar, and deer, could represent additional sources of infection for humans (41,43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HEV antibody prevalence among persons who work with swine [4] and among those who live in the rural southern of the People's Republic of China [13] has been reported. Renou et al and Colson et al reported the possible zoonotic transmission of HEV through direct contact between a pet pig and its owner, and from surgical training on pigs, respectively, in France in 2007 [3,23]. In swine, the duration of viremia after HEV infection is not very long [19].…”
Section: Discussionmentioning
confidence: 99%
“…The findings that genetically similar G3 and G4 HEVs have been isolated from pigs [21,23], deer and wild boars [15,20,31], and that serum antibodies to HEV were detected in a variety of animals including pigs [29], deer, wild boars, wild rats [10], dogs, cats, cows [18,26], and monkeys [1,2,6,8,33], suggest that hepatitis E is a zoonosis. Also, hepatitis E virus antibody prevalence among persons who work with swine [4] and among those who live in the rural, southern part of the People's Republic of China [13] has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…La consommation de viande de porc insuffisamment cuite ou de produits non cuits sous la forme de salaisons constitue donc un facteur de risque. Un contact direct avec des animaux infectés peut enfin être à l'origine d'infections comme cela a été récemment décrit à partir d'un petit cochon de compagnie [8]. La contamination directe de l'homme par l'animal est également étayée par une prévalence plus élevée d'anticorps anti-HEV chez les vétérinaires et les personnels d'élevages porcins que dans la population générale.…”
Section: Le Virus De L'hépatite E (Hev) Et Sa Variabilité Génétiqueunclassified
“…l'action des éléments de régulation de Nkx2.1, Gsh2 [7], et Dlx5/6 [8]. Chez les souris Celsr3|Foxg1, Celsr3 est inactivé dans le télencéphale mais pas dans le thalamus dorsal.…”
Section: Rôle De La Cadhérine Celsr3 Dans La Connectivité Du Cortex Cunclassified